Estudo de componentes de FIWARE para IoT e cidades inteligentes - Silva, Felipe Matheus Conceição da (2019)
The Internet of Things (IoT) is a technological concept that is gradually becoming established in people’s daily life, creating benefits that are not noticed, once they are integrated seamlessly as solutions. One example of these solutions are Smart Cities, which use data and technology provided by IoT to improve many aspects of urban life. A university is an environment that could be perceived as a small-scale representation of the needs of a city. In order to understand how to implement the solutions offered by the IoT and Smart Cities, this work intends to carry out a bibliographic study to list the challenges imposed by these technologies. As a way to understand how to overcome some of these challenges, a study on the FIWARE platform is also carried out, as this platform contains components designed specifically to facilitate the implementation of smart applications. Finally, this work proposes the implementation of a test application which simulates a smart classroom using the researched concepts and FIWARE components Orion Context Broker and IDAS (IoT Agents).